Karakteristik Mekanik Komposit Serat Pinang Matrix LDPE Dengan Variasi Massa Serat Pinang Tanpa NaOH dan NaOH - Parwa, I Kadek; Kencanawati, C.I.P.K.; Priambadi, IGN. (Teknik Desain Mekanika, 2022)
Abstract The development of an increasingly modern era can increase human resources to create new technologies, one of which is composites, composites are expected to be an alternative to metal as a construction material. This study used areca nut fibers with varying sizes with Low Density Polyethylene (LDPE) binder. In this study, bending testing (ASTM D790-03), impact testing (ASTM E23-07), and SEM (scanning electron microscope) observations were carried out. The highest impact test was found in the areca fiber composite LDPE matrix at Mass Fraction 5%: 2%: 3% NaOH treatment with an average value of 0.1966 Nm/mm². The mass fraction of 2% : 3% : 5% without NaOH treatment had the lowest impact strength value of 0.1089 Nm/mm². The impact strength of the LDPE betel nut fiber composite is influenced by the number of areca nut fibers whose size is 2 mm so that the fibers can fill the empty space and spread evenly. NaOH treatment on the fiber can remove lignin and wax layers that can cause voids in the composite so that it can affect the impact strength. The highest values for bending stress, bending strain and modulus of elasticity were found in LDPE betel nut fiber composites with a mass fraction of 5%: 2%: 3% NaOH treatment with an average value of 19.040 MPa, 0.011 mm and 2092.078 MPa. The lowest values of bending stress, bending strain and modulus of elasticity were LDPE betel nut fiber composites with a mass fraction of 2%: 3%:5% without NaOH treatment with an average value of 12.821 MPa, 0.008 mm and 1639.744 MPa. With a low number of areca fiber composition of 2 mm, it can cause voids so that it affects the value of bending stress and bending strain. The results of the SEM test showed an even bond between the matrix and areca fiber in the composite with a mass fraction of 5%: 2%: 3% because the total composition of the areca fiber was 2 mm which could fill the empty space in the composite and the NaOH treatment could prevent voids from occurring.. Keywords: areca nut, composite, low density polyethylene.